Nitrous oxide dynamics in the Arctic Siberian shelves of the North Kara Sea during summer 2021 - Muller, Sofia; Fripiat, François; Martínez-García, Alfredo; Jaccard, Samuel L.; Jens A. Hölemann; Delille, Bruno (2024)
info:eu-repo/semantics/nonPublished